A RACIONALIDADE COMUNICATIVA COMO MÉTODO DE DEBATE PARA EDUCAÇÃO EM DIREITOS HUMANOS NO ENSINO-APRENDIZAGEM DE FILOSOFIA - Oliveira, Ramando Carvalho (2020)
Using the action-research format, this dissertation under the title Communicative rationality as a debate model for Human Rights Education on Philosophy s teaching-learning , objective through an practical educational intervention performed together with